Politik Hukum Pencegahan dan Penanganan Politik Uang dalam Pemilu - Hariyanto, Hariyanto (Hukum dan Masyarakat Madani, 2021)
Money politics undermine democratic systems throughout the nation. Therefore, dealing with money politics is not enough for law enforcement alone, but also for all elements of society. The seriousness of the government and political parties in overcoming the problem of money politics can be done by means of political law. This study discusses political policy in money politics and political policy in money politics in the 2019 elections in the Banyumas district. The method in this study is a type of empirical normative research with descriptive qualitative methods and the research used in this research is descriptive-analytic. The research location of Banyumas Regency using purposive sampling method. The results showed; First, political policy in money politics in the 2019 Election in Banyumas Regency, political parties made several efforts in at least three things. 1) implementation the integrity pact and providing debriefing to cadres and legislative candidates. 2) all parties that consider only following the existing rules issued by KPU or Bawaslu institutions. 3) Related to the competency requirements of the more stringent legislative candidates, intellectuals, managerial skills, experience and morality are not all parties that require them. Second, the Legal Policy on Change and Political Policy in the 2019 Regional Election in Banyumas Regency, which is called the Regional Election has a strategy through Legal Policy, namely prevention of monetary policy level policies, judicial policies, transfer policies that have not been implemented can be realized